Molecular characterization of porcine Siglec-10 and analysis of its expression in blood and tissues. Issue 1 (January 2015) - Escalona, Z.; Álvarez, B.; Uenishi, H.; Toki, D.; Yuste, M.; Revilla, C.; del Moral, M. Gómez; Alonso, F.; Ezquerra, A.; Domínguez, J.
Highlights: Generation of cell lines expressing porcine Siglec-10. Development of monoclonal antibodies to porcine Siglec-10. Porcine Siglec-10 is mainly expressed on B cells in blood and tissues, and at low levels on monocytes. Abstract: Siglecs are sialic acid binding Ig-like proteins involved in the control of leukocyte responses. In this study we describe the characterization of a porcine orthologue of Siglec-10. A cDNA clone was obtained from a porcine library which encodes a protein with sequence homology to human Siglec-10. This cDNA codes for a type I transmembrane protein containing four Ig-like domains, a transmembrane region, and a cytoplasmic tail with three tyrosine-based motifs, including a membrane-proximal Grb2-binding motif, and two ITIM motifs. When expressed on transfected cells, porcine Siglec-10 was able to bind red blood cells in a sialic acid-dependent manner. Monoclonal antibodies were developed against this protein and used to examine its cell and tissue distribution in the pig. Siglec-10 was found to be expressed on blood B cells and B cell areas of the spleen and lymph nodes. A weak expression was also detected on monocytes.